Nine new species of Phoridae (Insecta: Diptera) from Spain - García-Romera, Carlos; Barrientos, Jose Antonio (Zootaxa, 2014)
One new species of Triphleba Rondani and eight new species of Megaselia Rondani are described from Montseny Natural Park (mainland Spain). The new species are Megaselia arbuciensis García-Romera sp.nov., Megaselia barrientosi García-Romera sp. nov., Megaselia callunae García-Romera sp. nov., Megaselia carminis García-Romera sp. nov., Megaselia ivanis García-Romera sp. nov., Megaselia longianalis García-Romera sp. nov., Megaselia montseniensis García-Romera sp. nov., Megaselia sarae García-Romera sp. nov., Triphleba beatricis García-Romera sp. nov.